Concomitant formation of protocells and prebiotic compounds under a plausible early Earth atmosphere - Christian Jenewein; Aurora Maíz-Sicilia; Fernando Rull; Lorena González-Souto; Juan Manuel García-Ruiz (Proceedings of the National Academy of Sciences, 2025)
Revealing the origin of life and unambiguously detecting fossil remains of the earliest organisms are closely related aspects of the same scientific research. The synthesis of prebiotic molecular building blocks of life and the first compartmentalization into protocells have been considered two events apart in time, space, or both. We conducted lightning experiments in borosilicate reactors filled with a mixture of gases mimicking plausible geochemical conditions of early Earth. In addition to the variety of prebiotic organic molecules synthesized in these experiments, we investigated the micrometer-thick silica-induced organic film that covers the walls of the reactors and floats at the water–gas interface. We found that the film is formed by aggregation of HCN-polymer nanoclusters whenever water is present, either in the liquid or vapor phase. The organic film morphs into micrometer-scale biomorphic vesicular structures hanging from the organic film into the water. We also show that these structures are hollow and may act as microreactors facilitating chemical pathways toward increasing complexity. We propose that these organic biomorphs form through a bubble-driven mechanism and interfacial precipitation of HCN-polymers. The concomitant synthesis of biomorphic poly-HCN protocells and prebiotic molecules under plausible geochemical conditions of early Earth-like planets and moons and opens a different geochemical scenario for the emergence of life. Our results suggest that the coexistence of molecular building blocks of life and submicron biomorphic structures in the oldest rocks on Earth or any other celestial body does not necessarily mean evidence of life.